2013
DOI: 10.1103/physreve.88.043204
|View full text |Cite
|
Sign up to set email alerts
|

Bright and peaklike pulse solitary waves and analogy with modulational instability in an extended nonlinear Schrödinger equation

Abstract: The modulational instability (MI) phenomenon in the nonlinear Schrödinger equation (NLSE) extended by two different nonlinear dispersion terms and the gradient term is investigated. We find that the possibility of instability of plane waves depends on the sign of the nonlinear dispersion parameters with regard to the linear dispersion coefficient. In contrast to the basic NLSE, the system may exhibit instability in the defocusing media for amplitude exceeding a critical value depending on the magnitude of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…It is interesting to note that the coefficients of cubic terms determine the similarity variables and the external potential. The expressions in (22) show that if Γ j = 0 the coefficients of quintic terms must be constant for the above conversion to work.…”
Section: The Model and Its Related Autonomous Systemmentioning
confidence: 98%
See 3 more Smart Citations
“…It is interesting to note that the coefficients of cubic terms determine the similarity variables and the external potential. The expressions in (22) show that if Γ j = 0 the coefficients of quintic terms must be constant for the above conversion to work.…”
Section: The Model and Its Related Autonomous Systemmentioning
confidence: 98%
“…Theorem 1: The governing equations of dynamics of the ultra-short pulse propagation along orthogonal polarization axes in nonlinear optical fibers with or without Kerr nonlinearities given by NLSEs (1)-(2) can be transformed under the transformation (5) into an autonomous system given by (3)-(4) provided that X, T , θ j , and ρ j (j = 1, 2) are given by (21), and the external potential is given by (17) and the coefficients of quintic terms satisfy the expressions given in (22).…”
Section: The Model and Its Related Autonomous Systemmentioning
confidence: 99%
See 2 more Smart Citations
“…Among all these fields, there are only a few systems where experiment studies are easily observed. In physics, precisely, nonlinear electrical transmission lines (NETL) [2][3][4] are good examples to provide a useful way to check how the nonlinear excitations behave inside the nonlinear medium. They are discrete systems but approximate the continuum systems quite well, as will be seen below [5].…”
mentioning
confidence: 99%